Agricultural research and poverty reduction - Hazell, Peter B. R.; Haddad, Lawrence J. (International Food Policy Research Institute, 2001)
International agricultural research has contributed enormously to increasing world food supplies to their current state of plenty. Yet poverty remains a major problem and the challenge for agricultural research now lies in developing strategies that more explicitly address the needs of the poor. This paper, based on the study commissioned by the Technical Advisory Committee (TAC) of the CGIAR system, addresses this issue. Based on an analysis of the links between agricultural research and poverty alleviation in different types of countries and rural regions, Peter Hazell and Lawrence Haddad identify six key priorities for a pro-poor agricultural research agenda and discuss strategies for achieving each of these goals with the least trade-off in national agricultural growth. (Excerpted from Forward by Per Pinstrup-Andersen and Emil Javier)